Factors associated with pregnant women's willingness to receive maternal pertussis vaccination in Guizhou Province, China: An exploratory cross-sectional study - Feng Jiang; Xingui Ye; Ying Wang; Ning Tang; Jun Feng; Yuanxue Gao; Meiling Bao (Taylor & Francis Group, 2024)
ABSTRACTThe rise in pertussis incidence among infants in Guizhou, China underscores the need for maternal acellular pertussis vaccine (aP) immunization, a key strategy in protecting infants from severe health consequences. However, the willingness of pregnant women in Guizhou to receive this vaccine is not well-understood. This study aimed to explore pregnant women's intentions toward maternal pertussis vaccination in Guizhou and identify the associated factors. A questionnaire based on the health belief model, was administered in an exploratory cross-sectional study from January to February 2022. Data from 564 participants were collected and analyzed. The chi-square test, Mann-Whitney U test, and Poisson regression were used to identify potential factors associated with vaccination intentions. Participants' median age was 27 y (interquartile range (IQR): 24-31), and the median number of children per participant was one. The study found that only 36.0% of the participants intended to receive the aP vaccine while 64.0% were uncertain or negative in this regard. Significant factors associated with intentions to vaccinate included perceived barriers and cues for action and perceived benefits. The major barriers for low vaccination intentions were safety concerns for both the fetus and the mother, and family members' negative attitudes. Free vaccines, perceiving preventive benefits, observing other pregnant women getting vaccinated, and healthcare provider recommendations may facilitate vaccination intentions. Multiple immune strategies should be developed or optimized to cope with the resurgence of pertussis.